2018
DOI: 10.1111/jgh.14117
|View full text |Cite
|
Sign up to set email alerts
|

Association of AlkB homolog 3 expression with tumor recurrence and unfavorable prognosis in hepatocellular carcinoma

Abstract: These findings reveal an important role of ALKBH3 in HCC, indicating that ALKBH3 could be used as a new therapeutic target in future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
3
10
0
Order By: Relevance
“…Western blot and immunohistochemistry staining were performed as previously described ( 19 ). For western blot assay, the primary antibodies against DUSP9 (1:2000, Abcam, cat.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blot and immunohistochemistry staining were performed as previously described ( 19 ). For western blot assay, the primary antibodies against DUSP9 (1:2000, Abcam, cat.…”
Section: Methodsmentioning
confidence: 99%
“…179467) were used in accordance with the manufacturer’s instructions. Signals were detected using an ECL kit (Pierce, Rockford, IL) as previously reported ( 19 ). For immunohistochemistry staining, primary antibodies against DUSP9 (1:200, Abcam, cat.…”
Section: Methodsmentioning
confidence: 99%
“…ALKBH4 belongs to the AlkB family of non-heme Fe (II)/a-ketoglutarate-dependent dioxygenases, whose function have been implicated in the repair of methylation damage in DNA and RNA (Lee et al, 2005). Available evidences also indicate that several members of AlkB family, such as ALKBH3 and ALKBH5, are closely linked to the inhibition of tumorigenesis and progression in various human cancers (Stefansson et al, 2017;Wang et al, 2018;Zhu et al, 2019). ALKBH4 has been previously illustrated in mediating demethylation of a monomethylated site in actin and depletion of ALKBH4 contributes to defects in cytokinesis and cell motility (Li et al, 2013), however, the underlying molecular mechanisms of ALKBH4 in tumor remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent research has identified another m 6 A demethylase, ALKBH3 (43). Wang et al (86) reported that ALKBH3 was overexpressed in HCC and high ALKBH3 expression in HCC tissues decreased OS and disease-free survival in HCC patients. ALKBH3 knockdown inhibited human HCC cell proliferation in vitro and xenograft tumor formation in vivo, presumably through p21/p27-mediated cell cycle arrest at the G1 phase (86).…”
Section: Erasers and Hccmentioning
confidence: 99%